Glass and Glass Sealants as Bioceramics - Bala, Indu (My University, 2008)
The optimization of bioactive glasses requires a proper understanding of chemical, physical mechanical and biological properties. The formation of a hydroxyapatite layer on silica based bioactive glasses has already been investigated by many researchers. In the present investigation, calcium based glasses of different composition have been synthesized by taking appropriate proportion of each oxide composition. The samples are charatererized by using the various techniques viz, X-ray diffraction (XRD), UV-Visible spectroscopy, and FT-IR, density and solubility measurements. The entire samples were dipped in simulated body fluid (SBF) solution for different time duration. Sample AS1 and AS3 show the formation of hydroxyapatite layer. On the other hand, samples AS2 and AS4 were not formed the hydroxyapatite layer. Apart from this, AS1 and AS3 samples also exhibit higher durability as compared to other two samples (AS2 and AS4).
M.Tech. (Materials Science and Engineering)
Keywords: Bioceramics, Glasses